CYBER NOTARY DALAM PERSPEKTIF KEPASTIAN HUKUM DAN PRINSIP KEHATI-HATIAN NOTARIS - Muh Fanny Chamdani; Nuzulia Kumala Sari; Moh. Ali (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The rapid evolution of information technology has catalyzed a paradigm shift in notarial services through the emergence of the cyber notary concept. Nevertheless, its integration into the Indonesian legal system remains obstructed by concerns over legal certainty and the stringent demands of the notary's duty of care or prudential principle. The objective of this research is to evaluate the regulatory framework of cyber notary in Indonesia, scrutinizing its execution through the lens of legal certainty and the adherence to the prudential principle in electronic notarial acts. Adopting a normative juridical methodology, this study utilizes statutory, conceptual, and comparative perspectives, supported by a qualitative analytical framework. The results indicate that the regulation of cyber notary in Indonesia remains incomplete and creates ambiguity concerning the validity and evidentiary strength of electronic notarial deeds. Furthermore, the prudential principle of notaries has expanded in the digital context, encompassing electronic identity verification, system security, and data protection. Therefore, regulatory reform, harmonization of laws, and enhancement of notarial competencies are necessary to ensure the proper implementation of cyber notary, providing legal certainty and adequate protection for all parties involved. ABSTRAK Perkembangan teknologi informasi telah mendorong transformasi dalam praktik kenotariatan melalui konsep cyber notary. Namun, implementasi konsep ini di Indonesia masih menghadapi berbagai permasalahan, terutama terkait kepastian hukum dan penerapan asas kehati-hatian notaris. Penelitian ini bertujuan untuk menganalisis pengaturan cyber notary dalam sistem hukum Indonesia, mengkaji implementasinya dari perspektif kepastian hukum, serta menelaah penerapan asas kehati-hatian notaris dalam praktik digital. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan perbandingan, serta dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa pengaturan cyber notary di Indonesia masih belum komprehensif dan menimbulkan ketidakjelasan terkait keabsahan serta kekuatan pembuktian akta elektronik. Di sisi lain, asas kehati-hatian notaris mengalami perluasan makna dalam konteks digital, yang mencakup verifikasi identitas elektronik, keamanan sistem, serta perlindungan data. Oleh karena itu, diperlukan reformasi regulasi, harmonisasi peraturan perundang-undangan, serta peningkatan kompetensi notaris guna mewujudkan implementasi cyber notary yang menjamin kepastian hukum dan perlindungan bagi para pihak.